The Development of Synectic Models in Learning Writing in Short Story in the Class XI of Medan UISU High School - Rini Sartika Nasution; Mutsyuhito Solin; Malan Lubis (BIRCU, 2020)
This research and development based on the phenomenon that there are still many students who have difficulty in writing short stories and the importance of educators innovating in the use of learning models in an effort to improve the achievement of learning objectives. This study aims to (1) Describe the process of developing synectic models in short story writing students in class XI students of UISU Senior High School Medan (2) Describe the feasibility of developing synectic models in learning to write short stories in class XI students of SMA UISU Medan (3) in learning to write short stories at XI grade students of UISU Medan High School. This type of research is development research based on the development model 4-D of Thiagarajan. The trial subjects consisted of material experts, design experts, Indonesian language educators, and XI grade students of UISU Medan High School. Validation results show an average percentage of 92.12% for learning material and an average percentage of 95.13 % for learning design with excellent advice. The effectiveness of the product is obtained from a learning motivation questionnaire in a limited trial and is supported. Limited trials show an average percentage of 93.45% with very good criteria and approval trials of 95.12% with very good criteria. The data is also supported by the observations of students also increasing the pretest value from 64.83 to the posttest with an average value of 80.47. This proves that the synectic model developed for learning to write short stories is feasible to use and can improve students' ability to write short stories.